A new species of cestode Lytocestus paithanensis (Lytocestus Cohn, 1908) from Clarias batrachus at Paithan, MS, India - Kale SS (International Journal of Life Sciences, 2017)
The present communication deals with description of new species Lytocestus paithanesis n.sp. is reported from Clarias batrachus at paithan Dist. Aurangabad. It difference from all known species of the genus, with the characters like, head is spatulate, narrower than body, broad base and narrow apex; neck medium, wide narrow anteriorly and posterioly wide; gonads located near the posterior end of the worm, testes 220-250 in number, oval, preovarian, scattered in middle of worm; ovary medium H- shaped; large ootype ; utrus tubular and wide.